Muir's textbook of pathology - Herrington, C. Simon (CRC Press, Taylor & Francis Group, 2014)
"Muir's Textbook of Pathology sets a standard in this subject by outlining the scientific aspects that underlie pathological processes, relating these to specific organ systems and placing all in a context that the student of medicine or pathology can appreciate and understand. The clearly defined and easy-to-follow structure, enhanced by numerous photographs and explanatory line diagrams, focus on core material without neglecting novel concepts and up-to-the minute detail. This one-stop-shop in pathology that will take the student right through medical school and beyond to postgraduate training." - Provided by Publisher